İSLAM MİMARİSİNDE GEOMETRİK BEZEME ÖNCÜLERİ VE İLK GEOMETRİK KOMPOZİSYONLARIN OLUŞUMU - (:unkn) unknown (My University, 2014)
İslam mimarisinde uygulanmış ilk geometrik desen oluşumlarını tarihsel süreç içinde ele almak ve ilk Müslüman-Türk devleti olan Karahanlılar'ın bu tezyinatın gelişmesindeki katkılarını ortaya koymak, makalemizin esasını oluşturmaktadır. Geometrik bezeme uygulamalarını, tuğla malzemenin tüm imkânlarından faydalanılarak hem yapı elemanı hem süsleme elemanı olarak kullanıldığı Karahanlı dönemi mimari eserlerinde daha sistemli görmekteyiz. Tuğlanın şeklinden de istifade ile zengin bir çeşitlilik oluşmuştur. İlk eserlerde daha basit uygulamalara fakat yine de çeşitliliğe yer verilmiştir. O dönemin zanaatkârlarının bu kompozisyonları nasıl uygulamış olabileceklerinden hareketle bu ilk örneklerin açılımına ilişkin yaptığımız çalışmaya makalede yer verilmiştir.

Raising concern over the scope of geometrical ornaments, approaching the formations of the very first geometrical patterns executed in the islamic architecture within the historical processing and putting forward the contributions of Karahanids, the first Turkic Islamic dynasty, to the development of these ornaments serves as the basis of this article. We observe geometrical ornaments exploiting all of the facilities of the brick both as a structural element and as a decorating element implemented more systematically in the architectural works of the Karakhanid era. Benefiting also from the shape of brick, a rich diversity was originated. The implementations included in the first works were simpler than the fallowing ones ( e.g.13th and 14th century) however they were of great variety . In this article, based on how the craftsman of that period executed these compositions, we also gave place to our work on the expansions of these first examplers.
The Pioneers of Geometric Designs and the Formation of Geometric Compositions in Islamic Architecture
Keywords: Sanat; Tarih